Implementasi Penyelesaian Wanprestasi Dalam Perjanjian Kredit Perbankan Pada Masa Pandemi Covid-19 Di BPR INSUMO Sumberarto Kediri - Nurbaedah (Universitas Serang Raya, 2021)
Credit activities in the banking sector, especially People's Credit Banks during the COVID-19 pandemic are allegedly experiencing a level of sluggishness and indications of the emergence of credit problems, especially in legal certainty for parties who bind themselves to credit so as to give birth to achievements that must be carried out in accordance with the agreed time period. certain. If there are parties who are found to have violated their achievements or do things that should not have been done outside the agreement, then the violators are declared to have committed wan achievements. The purpose of this study is to find out what settlements can be made if the debtor breaks his promise (wan achievement), and to analyze the obstacles in credit settlement at PT BPR Insumo Sumberarto Kediri. The research method used is descriptive analytical research method with an empirical juridical approach. The result of this research is that the procedure for granting credit at PT BPR Insumo Sumberarto Kediri consists of four stages, namely the credit application stage, the credit analysis stage, the credit decision stage and the credit disbursement stage. Takeover of collateral as a credit settlement process if the debtor breaks his promise (wan achievement). Obstacles in credit settlement at PT BPR Insumo Sumberarto Kediri are normative barriers (related to Law Number 8 of 1999 concerning Consumer Protection), internal barriers (poor system performance from banking institutions) and external obstacles (arising from the debtor himself).